Analisis Penetapan Perkara NO. 916/PDT.P/2022/PN.SBY Pengadilan Negeri Surabaya Perihal Pernikahan Pasangan Beda Agama - Nurullah, Aris; Atmari, Atmari; Quddus , Abdul; Ihya, Rahmat (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2025)
Some marriages in Indonesia cause legal polemics and social polemics that should be in accordance with national law, especially in article 2 (1) in marriage law No. 1 of 1974 concerning marriage. Case No. 916/PDT. P/2022/PN. SBY is important related to understanding how court guidelines decide on marriages of different religions. This research aims to understand the legal basis and judges' considerations as well as the impact or social implications on the determination issued by the court in the case, as well as provide recommendations in overcoming the legal vacuum related to interfaith marriage, this research is a juridical normative research with a qualitative method, by using primary data, documents of the Surabaya State Religious Court, as well as secondary data obtained from several documents, both literature and Scientific journals, from the data will be analyzed in a descriptive analysis, related to understanding the relationship between positive legal aspects and social values that live and develop in society. The results of the research show that the determination of No. 916/PDT. P/2022/PN. SBY is based on the implementation of legal principles, and human rights by taking into account the applicable legal provisions and the social situation of the parties. This determination reflects the need for a revision of the marriage law to be more inclusive of the reality of religious diversity/pluralism in Indonesia